Comparative Evaluation Study of II2 O2 Mouthrinse in Gingivitis - Haghighati F; Nezam Abadi Sh (Tehran University of Medical Sciences, 1999)
Bacteria! plaque is an essential factor of gingival and periodontal disease."nThe ability of chemical piaque control agent to prevent plaque formation is well documented compare with"nother mechanical plaque removal methods. The purpose of this study was to compare clinical effects of"nShore choice mouth rinse (H2 O2, 0.1%) with a placebo."nFollowing a period of 4 weeks, 20 subjects were allocated to two treatment groups."nDuring this period of time, they rinsed twice a day with either a placebo mouth rinse or the Shor choice."nPlaque Index (PI) and bleeding on probing index (BOP) were recorded three days after scaling and root"nplanning. These indecies were rechecked 2 and 4 weeks after rinsing the subject's mouth by mouth rinse and"nplacebo. Results indicated that although there were no significant differences between test and control"ngroups, a reduction of PI and BOP were found in different stages of this study."nThe clinical data obtained in this study are thus consistent with the previous data, however, care should be"ntaken to extrapolate these results.